2013
DOI: 10.1002/poc.3162
|View full text |Cite
|
Sign up to set email alerts
|

Amination of phenylketenes. Substituent effect on amine‐catalyzed tautomerization of amide enol

Abstract: The transient intermediates with infrared bands at 1676-1680 cm À1 observed for reaction of substituted phenylketenes with diethylamine in acetonitrile were suggested to be the amide enols rather than the zwitterions on the basis of the theoretical calculations. A single broad band at 1674 cm À1 observed for reaction with the primary amines was attributed to overlap of two bands of the intermediate (amide enol) and the final product (amide). The substituent effect for the second-order rate constants of diethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 42 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…57 Only a few examples are known in the literature. [58][59][60][61] Hegarty et al 62 as well as Wagner et al 63 suggested the formation of amide enols as intermediates in the hydration of arylketene imines and amination of arylketenes by transient time-resolved spectroscopy. Frey and Rappoport showed the synthesis and NMR spectrum of a conjugated amide enol with bulky substituents (Tip 2 ]C(OH)NMe 2 , tip ¼ 2,4,6-triisopropylphenyl) in solution by addition of diethylamine to the corresponding aryl substituted ketene.…”
Section: Introductionmentioning
confidence: 99%
“…57 Only a few examples are known in the literature. [58][59][60][61] Hegarty et al 62 as well as Wagner et al 63 suggested the formation of amide enols as intermediates in the hydration of arylketene imines and amination of arylketenes by transient time-resolved spectroscopy. Frey and Rappoport showed the synthesis and NMR spectrum of a conjugated amide enol with bulky substituents (Tip 2 ]C(OH)NMe 2 , tip ¼ 2,4,6-triisopropylphenyl) in solution by addition of diethylamine to the corresponding aryl substituted ketene.…”
Section: Introductionmentioning
confidence: 99%